A substituição do ICMS pelo IBS, nos termos da Emenda Constitucional nº 132/2023: principais alterações - Caballero, Maria Clara Vizotto (2024)
The present work refers to a tax analysis regarding the substitution of ICMS by IBS, under the terms proposed by Constitutional Amendment nº 132/23. The objective of this work will be to glimpse the main changes that the new legal text introduces to our tax system, mainly from the perspective of the current situation of taxation on consumption and the main differences that we can observe between ICMS and IBS. The study is justified by its current nature and by creating a new form of taxation on consumption in the country, which must be very well scrutinized so that it does not make the same mistakes made in the past in relation to the concepts of social justice and fiscal federalism. To this end, we will analyze the constitutional profile of ICMS and IBS, in addition to the basic concepts of federalism and tax jurisdiction, based on the understandings established by the doctrine and guidelines established in legal diplomas. In the end, it will be possible to conclude that the approval of Constitutional Amendment nº 132/23 and the institution of IBS in Brazil is just a reformulation of our tax system, which was already obsolete, and brings a positive perspective to the future of the countr